Training volume, heart rate variability, and injury risk in CrossFit athletes - Skae, Kieran Robert Albert (Rhodes University, 2026)
CrossFit, a high‑intensity functional fitness program, has increased in popularity worldwide. Yet, systematic research into injury risk among non‑elite participants and studies on interventions to reduce injury rates and mitigate risk factors remain limited. Reported injury rates and preventative strategies vary widely, leaving a critical evidence gap, particularly in under‑studied regions such as South Africa. This dissertation addresses this gap through two complementary phases guided by the Translating Research into Injury Prevention Practice (TRIPP) framework. Study one, a sixteen-week, observational study, included 33 non-elite CrossFit athletes who completed weekly online injury surveys using the adapted Oslo Sports Trauma Research Centre (OSTRC) Overuse Injury Questionnaire. Participants’ training volume (TV) was monitored using acute to chronic training volume ratios (A:C ratios), where acute training volume was the sum of session rating of perceived exertion (sRPE) and session duration over the most recent week, and chronic training volume was the three‑week rolling average. Heart rate variability (HRV) was assessed daily via the HRV4Training application. Although no statistically significant findings were identified between TV, HRV, and injury risk, the relatively small sample size and exploratory nature of the study warrant cautious interpretation of these findings. Injury was, however, significantly associated with demographic and behavioural factors (age, male sex, training frequency, and commitment), and injury likelihood progressively increased over the study period. Study two (scoping review) was conducted according to the PRISMA Extension for Scoping Reviews (PRISMA-ScR) and Joanna Briggs Institute guidelines. The literature search was performed across seven databases: MEDLINE, Academic Search Complete, and Health Source – Consumer Edition (via EBSCO), PubMed, SCOPUS, Science Direct, and Web of Science. Findings revealed limited structured interventions, predominantly focusing on warm-up and cool-down protocols, nutritional supplementation, protective exercise gear, mobility programmes, HRV monitoring, and education approaches. The findings also highlighted inconsistent injury definitions, high methodological variability, and underrepresentation of specific athlete populations. Collectively, these findings emphasise the need for advanced CrossFit injury research beyond risk identification (TRIPP stages one and two), shifting towards structured and inclusive investigations of preventative strategies (stages three to six). Future research should prioritise methodologically robust studies, standardise data collection methods, and evaluate multifactorial injury prevention strategies to enhance the safety and sustainability of CrossFit participation.
identifying risk factors and intervention strategies
Keywords: Uncatalogued